Personality and Functional Vision in Older Adults with Age-Related Macular Degeneration. (May 2014) - Rovner, Barry W.; Casten, Robin J.; Hegel, Mark T.; Massof, Robert W.; Leiby, Benjamin E.; Ho, Allen C.; Tasman, William S.
Introduction: The purpose of the study was to determine whether personality traits influence self-reported functional vision in patients with age-related macular degeneration (AMD). Methods: This is a prospective cross-sectional analysis of baseline data from the Low Vision Depression Prevention Trial. Participants ( N = 182) over age 65 with bilateral AMD, visual acuity worse than 20/70 in the better-seeing eye, and subthreshold depression were recruited from the Wills Eye Hospital retina practice. Assessments included visual acuity, contrast sensitivity, National Eye Institute Visual Function Questionnaire–25 plus Supplement (NEI VFQ–25) near and distance subscales, depression, and personality testing. Structural equation models were used to investigate the relationship of the NEI VFQ near activities and distance activities with the various demographic, clinical, and psychological predictors. Results: In the single-predictor model for near functional vision, visual acuity at logMAR ≤ 1 (estimate = −0.33 [95% confidence interval CI −0.46, −0.20]; p ≤ 0.001), neuroticism (estimate = −0.05 [95% CI −0.08, −0.01]; p = 0.01), and education (estimate = −0.08 [95% CI 0.01, 0.15]; p = 0.03) were statistically significant predictors. In the single-predictor model for distance functional vision, only visual acuity at logMAR ≤ 1 (estimate = −0.49 [95% CI −0.69, −0.29]; p ≤ 0.001) and neuroticism (estimate = −0.09 [95% CI −0.15, 0.02]; p = 0.008) were statistically significant predictors. Discussion: Self-reported functional vision depends on the severity of vision loss as well as the personality trait of neuroticism. Implications for practitioners: Assessment of personality traits, particularly neuroticism, may increase the precision of rating scales of functional vision and suggest new rehabilitative interventions to improve the functional vision and quality of life of patients with AMD.